Metode Dalam Pembelajaran Bahasa Arab - Mardhatillah Syahril; Puput Nurshafnita; Fauziah Nasution (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
Students of Arabic are those whose native language is not Arabic and who have been taught the language in schools. There are those who believe that Arabic is a challenging topic. The implementation of strategy and techniques for learning Arabic is carried out so that participants' pupils can acquire knowledge and information in a manner that is both more effective and efficient. When learning is going to be carried out, several teaching and learning strategies need to be created and put into action. Utilization of various approaches and procedures Learning Arabic in an effective and efficient manner will lead to optimum information retention, which will ultimately result in an improvement in the language's overall learning quality. When formulating a plan, several aspects of the plan need to be given careful consideration. These aspects include preparatory learning activities, the transmission of information, student participation, assessments, and advanced activities. The selection of learning strategies is determined based on strategic orientation criteria on learning tasks, their relevance with learning materials, methods and techniques that can focus on the goals to be achieved, and learning media that can stimulate the senses of students. This selection process takes place. Learning Arabic can be accomplished by a variety of methods, the most common of which are the grammatical way of translation, the direct method, the method reading, the audiolingual method, and the eclectic method. Key words: Method, Learning Arabic